2009
DOI: 10.1152/ajpgi.90468.2008
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of stellate cells by injured acinar cells: a model of acute pancreatitis induced by alcohol and fat (VLDL)

Abstract: MG. Stimulation of stellate cells by injured acinar cells: a model of acute pancreatitis induced by alcohol and fat (VLDL). Am J Physiol Gastrointest Liver Physiol 297: G1163-G1171, 2009. First published September 24, 2009 doi:10.1152/ajpgi.90468.2008.-Mechanisms leading to acute pancreatitis after a fat-enriched meal combined with excess alcohol are incompletely understood. We have studied the effects of alcohol and fat (VLDL) on pancreatic acinar cell (PAC) function, oxidative stress, and repair mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 32 publications
(38 reference statements)
1
22
0
Order By: Relevance
“…It is known that pancreatic stellate cells (PSCs) are activated by ethanol and its metabolites, and also by cytokines and oxidant stress, in the process of pancreatic fibrosis 45. Only a few detailed studies of pancreatic fibrosis using obesity models or high-fat–fed animals have been reported 46,47.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that pancreatic stellate cells (PSCs) are activated by ethanol and its metabolites, and also by cytokines and oxidant stress, in the process of pancreatic fibrosis 45. Only a few detailed studies of pancreatic fibrosis using obesity models or high-fat–fed animals have been reported 46,47.…”
Section: Discussionmentioning
confidence: 99%
“…However, no previous study of either animal models or human patients has evaluated the histological changes that occur during the transition from pancreatic fat accumulation to fibrosis. In the only study to have used acinar cells isolated from Wistar rats, very low-density lipoprotein was shown to induce acinar cell injury in the absence of alcohol, with subsequent PSC proliferation and synthesis of extracellular matrix 45. In the present study, temporal histological changes in the pancreatic tissue of ZDF rats were evaluated for the first time, and it was found that fat accumulation in acinar cells and subsequent pancreatic fibrosis appeared to increase upon chronic exposure to a high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…5 Since the first identification of PSCs, numerous in vivo and in vitro studies have provided strong evidence of a central role of PSCs in pancreatic fibrogenesis associated with chronic pancreatitis and pancreatic cancer. [5][6][7][8][9][10][11][12] Fibrotic responses to inflammatory insults may also be important in pathological responses in the endocrine portion of the pancreas, the islets of Langerhans. Islet fibrosis has been demonstrated in the pancreas of humans with T2DM, and in a number of animal models of diabetes, [13][14][15][16][17][18] where it is associated with the late stage of β cell failure during the progression to T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from alcohol, animal models have shown that chronic high fat diets in rats induce fibrogenesis too [76, 77]. In vitro studies [78], rodent models using high fat diets [76, 79] and studies on tissue from patients with chronic pancreatitis support lipid peroxidation products to play a role in stellate cell activation and fibrogenesis. The predominant collagen present in fibrous tissue, produced by the PSC is type I collagen [8082], with other components of the ECM being mainly proteoglycans.…”
Section: Pancreatic Fat and Chronic Pancreatitismentioning
confidence: 99%